A new phosphatized ophiuroid from the lower Triassic of Nevada and its position in the evolutionary history of the Ophiuroidea (Echinodermata) - Thuy, Ben; Maxwell, Vivienne; Pruss, Sara B. (Zootaxa, 2021)
The Lower Triassic fossil record of brittle stars is relatively rich, yet most records published to date are based on poorly preserved or insufficiently known fossils. This hampers exhaustive morphological analyses, comparison with recent relatives or inclusion of Early Triassic ophiuroid taxa in phylogenetic estimates. Here, we describe a new ophiuroid from the Lower Triassic of Nevada, preserved as phosphatized skeletal parts and assigned to the new taxon Ophiosuperstes praeparvus gen. et sp. nov Maxwell, V. & Pruss. S.B. This unusual preservation of the fossils allowed for acid-extraction of an entire suite of dissociated skeletal parts, including lateral arm plates, ventral arm plates, vertebrae and various disk plates, thus unlocking sufficient morphological information to explore the phylogenetic position of the new taxon. Bayesian phylogenetic inference suggests a basalmost position of O. praeparvus within the Ophintegrida, sister to all other sampled members of that superorder. The existence of coeval but more derived ophiuroids suggests that O. praeparvus probably represents a member of a more ancient stem ophintegrid group persisting into the Early Triassic.